Membrane reconstitution studies on the irreversibility of inactivation of sarcoplasmic reticulum of rabbit skeletal muscle - Arendse, Michael Peter (University of Cape Town, 2018)
Mild acid treatment or incubation in the presence of Ethylene glycol bis (β-aminoethyl ether) - N,N' - tetraacetic acid inactivates calcium transport by sarcoplasmic reticulum membranes but does not inhibit calcium stimulated ATPase activity. This inactivation is apparently irreversible. The purpose of the present study was to determine whether lipid-protein interactions, imposed by the transmembrane nature of the (Ca²⁺, Mg²⁺) - ATPase contributed towards the irreversible nature of the inactivation. This was determined by studying the possibility of reactivating calcium transport in acid-inactivated sarcoplasmic reticulum vesicles by means of membrane reconstitution studies. Calcium transport activity was reconstituted in control and acid-inactivated sarcoplasmic reticulum vesicles by deoxycholate solubilisation and subsequent slow dialysis at room temperature. Reconstituted control sarcoplasmic reticulum had an average specific activity of 0,38 μmol calcium transported /minute /mg of protein. Acid-inactivated sarcoplasmic reticulum vesicles, in which calcium transport had been inactivated to 0.2 μmol Calcium transported/minute/mg of protein (10% of the original transport activity) were studied by reconstitution methods. Following reconstitution, the isolated, reformed vesicles regained up to 1,5-fold transport activity when compared with the original acid-inactivated vesicles, indicating that acid-inactivation was partially reversible. Protein composition of reconstituted control and reconstituted acid-inactivated sarcoplasmic reticulum vesicles was studied by SDS-gel electrophoresis. Both preparations showed that the M55 protein was incorporated into reconstituted vesicles whereas there was a preferential loss of the M45 calcium binding protein (calsequestrin). The removal of deoxycholate into the dialysate was studied by means of (Carboxyl-C¹⁴) -deoxycholate. The kinetics of removal indicate that approximately 0,15 mg DOC remained associated per mg of protein even after exhaustive dialysis. Calcium efflux from reconstituted vesicles was followed by release of calcium into Ethylene glycol bis (β-aminoethyl ether) -N, N' -tetraacetic acid following active uptake in the presence of precipitable phosphate anions. Calcium efflux was slower from reconstituted vesicles than from original sarcoplasmic reticulum. The ability of acid-inactivated sarcoplasmic reticulum to bind Ca²⁺ or adenine nucleotides tightly was investigated. The capacity to bind calcium tightly was decreased from 1.43 nmol Ca²⁺/mg protein in control to 0,96nmol Ca²⁺/mg protein in acid inactivated sarcoplasmic reticulum. Similarly, the capacity to bind adenine nucleotides tightly decreased from 0,20 mol nucleotides/mol ATPase in control vesicles to 0,07 mol nucleotides /mol ATPase in acid inactivated vesicles. Following reconstitution the capacity for tight binding of calcium and adenine nucleotides increased to 2,4 nmol Ca²⁺/mg protein and 0,24 mol nucleotides/mol ATPase respectively indicating that the capacity to bind both calcium and adenine nucleotides tightly is closely related to transport activity but not to calcium dependent ATPase activity. These studies indicate that the protein-lipid interaction restrains the acid-inactivated sarcoplasmic reticulum from returning to its native conformation. Release of these constraints by deoxycholate followed by its removal results in reversal of the conformational change to that of the coupled native sarcoplasmic reticulum membrane.